Green Lanterns. Vol. 1, Rage planet - Humphries, Sam; Johns, Geoff, 1973-; Van Sciver, Ethan; Benes, Ed; Rocha, Robson; Wright, Jason (Jason St. John); Blond; Lanham, Travis; Sharpe, Dave (Letterer); Hi-Fi Colour Design (2017)
"A part of DC Rebirth! New Green Lanterns Jessica Cruz and Simon Baz debut a new era of emerald greatness, tackling the universe's toughest beat: Earth. These rookie Lanterns promised to protect others in brightest day or blackest night, but as the "Red Planet" begins to rise, the duo finds themselves confronted with an unimaginable threat from Bleez and the Red Lanterns! Rising star writer Sam Humphries (PLANET HULK, STARLORD) and artist Robson Rocha (EARTH 2: WORLDS END, BIRDS OF PREY) put on the rings with GREEN LANTERNS VOL. 1"--
Green Lanterns: rebirth / Geoff Johns and Sam Humphries, writers ; Ethan Van Sciver and Ed Benes, artists -- Rage planet: part 1 / Sam Humphries, writer ; Robson Rocha, penciller -- Rage planet: part 2 / Sam Humphries, writer ; Robson Rocha, penciller -- Rage planet: part 3 / Sam Humphries, writer ; Robson Rocha, Tom Derenick, Jack Herbert and Neil Edwards, pencillers -- Rage planet: part 4 / Sam Humphries, writer ; Robson Rocha, Ed Benes and Tom Derenick, pencillers -- Rage planet: part 5 / Sam Humphries, writer ; Robson Rocha and Eduardo Pansica, pencillers -- Rage planet: part 6 / Sam Humphries, writer ; Will Conrad and Jack Herbert, artists.
"Originally published in single magazine form in Green Lanterns Rebirth 1 and Green Lanterns 1-6"
Keywords: Green Lantern -- (Fictitious character) -- Comic books, strips, etc; Superheroes -- Comic books, strips, etc; Comic books, strips, etc. -- United States; Graphic novels; Superhero comics; Comics (Graphic works)